Doing history that matters: Going public and activating voices as a form of historical activism. Issue 1 (17th November 2020) - Dyck, Erika
Abstract: For many of us academics, doing community‐engaged research means coming to terms with the significant gaps in experience, privilege, and power, and overall access to knowledge. We are trained to learn through texts, not through direct experience. In some ways, we are even conditioned to tune out experience, or anecdote, to dilute personal subjectivities in favor of a critical analysis informed by a combination of methods and sources, and a reliance on text‐based forms of evidence. Whereas for most community members, evidence is experiential. This dynamic also underscores the tremendous power and responsibility we have as historians to shape identities and legacies through the stories we tell. In the end, I believe the risks are worth the rewards.